A Textual Analysis of the Masculinities Portrayed in Hook (Steven Spielberg, 1991) - Díaz-Cuesta, José; Asensio Aróstegui, Mar; Caldevilla Domínguez, David (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
This article focuses on the masculinities shown throughout Steven Spielberg’s Hook, following Pat Kirkham and Janet Thumim’s four sites of masculinities in film. Robin Williams’s character (Peter Banning/Pan) evolves from belonging to the business man prototype (Peter Banning) to becoming an adult-although-rejuvenated Peter Pan. His body is shown in action when BanninG/Pan attempts to behave in a more juvenile way. Banning/Pan’s external world is defined by his fatherhood, which involves both quality and quantity time spent with his children. The internal world is related to Banning/Pan’s fear of flying and death.